INFLUENCE OF CELEBRITY ENDORSER TOWARDS PURCHASE INTENTION ON SMARTPHONE SAMSUNG IN INDONESIA - Nimah Sakinah (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Serang Raya, 2020)
Celebrity endorsers is one of the effective marketing communications to attract consumers' attention, because celebrity endorsers have special dimensions such as attractiveness, expertise, and trustworthiness. The purpose of this research is to find out how much the influence of celebrity endorser on purchase intention on Samsung smartphones and how much the dimensions of attractiveness, expertise, and trustworthiness contribute to formation of celebrity endorser variables. Method of this research use a quantitative method by distributing online questionnaires via Google Form to 400 respondents. The data analysis technique is Structural Equation Modeling (SEM) assisted by SmartPLS software 3.3.2. The results of hypothesis testing found that there is a positive and significant relationship between celebrity endorser to purchase intention. In addition, the dimensions of attractiveness, expertise, trustworthiness have been proven to contribute positively to the formation of celebrity endorser variables. The expertise dimension has the biggest contribution to the formation of celebrity endorser variables. It can be concluded that all hypotheses in this study can be accepted. Key Words : Celebrity Endorser, Purchase Intention, Attractiveness, Expertise, Trustworthiness.